E-health system characteristics, medical performance and healthcare quality at UNRWA-Palestine health centers - Dahleez, Khalid Abed; Bader, Imad; Aboramadan, Mohammed (Journal of enterprise information management, 2021)
PurposeThis study aims to investigate how e-health system characteristics (information quality, system quality, perceived ease of use, perceived usefulness) contribute to the enhancement of medical staff performance, patient care, and doctor–patient relationships at UNRWA-Gaza healthcare centers. It aims at testing an integrative single model comprising Technology Acceptance Model (TAM), D&M model and e-health system utilization.Design/methodology/approachThis study followed the quantitative methodology and the deductive research approach. Data were collected from 241 medical staff who use the system employed in 19 different healthcare centers across the Gaza Strip. Partial least square/structural equation modeling technique was used to analyze the collected data and to test study hypotheses.FindingsStudy concluded that information quality of the adopted Health Information System (HIS) has both direct and indirect positive impact on staff performance, only direct positive impact on patient care and only positive indirect impact on doctor–patient relationship. System quality, on the other hand, was found to have negative direct impact and positive indirect impact on staff performance and has both direct and indirect positive impact on both doctor-patient relationship and patient care.Research limitations/implicationsNoteworthy that HIS has availability, speed and error detection and error prevention issues. It is recommended that these shortfalls be addressed together with improving user perception towards ease of use and usefulness of the system.Practical implicationsManagement should also work to raise confidence in its medical staff to improve the effect of HIS on medical performance and patient care. It is also recommended that UNRWA should implement crowed management techniques such as queuing systems and on-phone booking to minimize patient waiting time.Originality/valueThe importance of the study stems from its context being conducted in a developing region (Gaza Strip-Palestine) which has a fragile economic, political and social environment with many other complexities. It is also conducted at United Nations Relief and Work Agency (UNRWA) healthcare centers, which provide medical services to Palestinian refugees. In addition, this study is among the few studies that address the impact of individual e-health success factors on both doctor-patient relationship and patient care constructs. Most previous studies concentrated on the impact of health system adoption as a whole on these two subject variables and one can hardly ever stop at studies that address effect of individual success factors on them. It also integrated both D&M system success model and TAM model with some additional amendments creating and tested a new model.